Method modification for monitoring the scope of development project of complex technical system - Крицкий, Дмитрий Николаевич; Погудина, Ольга Константиновна; Дружинин, Евгений Анатольевич; Ченарани, Али (Technology audit and production reserves, 2016)
The method for monitoring the scope of development project of complex technical system was modified. This method can be used for the interim quality evaluation and financial justification of the result at all stages of development. The current monitoring methods were analyzed and it was concluded about the need to provide more information on the technical implementation of the project. The method of earned value got a further development for analysis of the data for the hypotheses and verified solutions offered by designers and technologists in various stages of development of complex technical systems. The system of inequalities for monitoring indicators of quality of the project content is proposed. This system of equations was taken into account peculiarities of the creation of complex technical systems: quality of these projects is determined by the result – a project product; costs are compensated during the operational phase; payback time shall be compared with the technical resource of project product; resources of the organization should be enough for the project realization. Experimental data of using this method in a scientific research institute of physical modeling problems were obtained. Using a modified method reduced development time up to 21 %.